The Impact of Urban Development on Coastal Community Health: A Qualitative Study in Makassar City - Ayu Indira Sangaji; Muhammad Syukur; Firdaus W Suhaeb (JUPE : Jurnal Pendidikan Mandala, 2026)
Urban development in the coastal areas of Makassar City has experienced rapid growth, resulting in significant environmental, social, and economic changes within the community. This study aims to analyze the impact of urban development on the health of coastal communities using William Cockerham’s health sociology perspective. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation. The findings indicate that urban development has led to environmental changes in coastal areas, including pollution and the reduction of fishing grounds, which contribute to increased health risks. In addition, changes in the economic structure have affected the community’s ability to access healthcare services. Social, economic, and environmental factors emerge as the primary determinants shaping the health conditions of coastal communities. This study emphasizes that public health is not solely influenced by medical factors, but also by social structures and development policies.